2001
DOI: 10.1017/s0952836901000838
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fish abundance on the otter (Lutra lutra) populations in Iberian Mediterranean habitats

Abstract: Recent studies show that the availability of prey in¯uences the ecology of otters by regulating breeding, carrying capacity and mortality. Mediterranean habitats experience extreme seasonal variation in water ow ± a stress period can occur in summer when water¯ows and levels are low with long periods of drought, while torrential¯oods usually occur in autumn and spring. Reservoirs can affect this situation by further in¯uencing water¯ow regimes and acting as a barrier. Our data show the close relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
66
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 24 publications
8
66
0
4
Order By: Relevance
“…These have shown that desiccation influences the availability of prey such as fish, which again may strongly affect the European otter (Lutra lutra) (Clavero et al, 2003;Ruiz-Olmo and Jiménez, 2009). Consequently, the mortality rate of otters increases, their abundance diminishes, and breeding success declines (e.g., Ruiz-Olmo et al, 2001). Furthermore, due to summer droughts, the breeding time of otters occurs earlier in Mediterranean than in temperate streams (Ruiz-Olmo et al, 2002).…”
Section: Biotic Responses To Flow Intermittencymentioning
confidence: 99%
“…These have shown that desiccation influences the availability of prey such as fish, which again may strongly affect the European otter (Lutra lutra) (Clavero et al, 2003;Ruiz-Olmo and Jiménez, 2009). Consequently, the mortality rate of otters increases, their abundance diminishes, and breeding success declines (e.g., Ruiz-Olmo et al, 2001). Furthermore, due to summer droughts, the breeding time of otters occurs earlier in Mediterranean than in temperate streams (Ruiz-Olmo et al, 2002).…”
Section: Biotic Responses To Flow Intermittencymentioning
confidence: 99%
“…Accordingly, the otter may be considered a generalist aquatic predator, even though only a few studies have simultaneously compared otter diet to food availability (Lanszki & Körmendi 1996;Carss et al 1998;Lanszki et al 2001;Ruiz-Olmo et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In this region, otters can frequently occur in almost dry rivers, provided that some ponds exist; this is not directly related to the availability of water itself, but to the availability of prey, which include mostly aquatic species (Ruiz-Olmo et al 2001;Ruiz-Olmo et al 2007).…”
mentioning
confidence: 99%
“…The reduction in the amount of water during these periods also increases the risks associated with foraging, as the otters need to look for food more frequently in shallow areas or out of water, where semi-aquatic species are weaker competitors than terrestrial species, and become more vulnerable to predation and to becoming roadkill (Ruiz-Olmo et al 2001;Ruiz-Olmo & Jiménez 2008b). The reliance on ponds also makes them more vulnerable to being harassed and killed by local fishermen (Carrillo-Rubio & Lafón 2004).…”
mentioning
confidence: 99%